Select Radio Programmes and Fight Against Child Violence in Owerri Metropolis, Imo State, Nigeria - Adeline, Nkwam-Uwaoma; Ifeoma, Ojiakor; Williams, Etumnu Emeka (Advances in Social Sciences Research Journal, 2021)
The issue of child violence has continued to plague Nigerian society and if care is not taken, the future of Nigerian society will be in serious jeopardy. To this end, this study investigated radio programmes and the fight against child violence in Imo State. The agenda setting theory served as the theoretical foundation of the study. The survey research method was used with a population of 555,500 of Owerri metropolis residents. The Survey Monkey online sample size calculator was used to arrive at 384 as the sample size. The Multistage sampling technique was adopted with a questionnaire as the instrument of data collection. The percentage method was used for data analysis. Findings revealed that 52% of the respondents confirmed that they were exposed to radio programmes on the issue of child violence at a moderate level. Also, at an average of 53% of respondents are of the view that the programmes have enhanced their knowledge of the issues of child violence at a moderate level. Further findings showed that an average of 53% of respondents confirmed that Because I am Happy on Groove 98.1 FM and the Mega Kid hour on Megaband 97.3 FM are effective in the fight against child violence in Imo State. It was recommended that radio stations should step up their efforts to raise awareness of programmes dealing with child violence and other child-related issues, so that the level of exposure increases significantly and contributes to the fight against child violence. To improve the knowledge of people about child violence and other child-related issues. Radio stations should do well by constantly educating and enlightening people through their programmes designed to treat issues of child violence and other child-related issues. Radio stations, through their programmes, should endeavour to sustain their efforts to continue being effective in the fight against child violence, so that in no distant time, the issue of child violence and other child-related issues will be reduced drastically in society.